Vital and dispensable roles of Plasmodium multidrug resistance transporters during blood‐ and mosquito‐stage development. Issue 1 (23rd May 2016) - Rijpma, Sanna R.; van der Velden, Maarten; Annoura, Takeshi; Matz, Joachim M.; Kenthirapalan, Sanketha; Kooij, Taco W. A.; Matuschewski, Kai; van Gemert, Geert‐Jan; van de Vegte‐Bolmer, Marga; Siebelink‐Stoter, Rianne; Graumans, Wouter; Ramesar, Jai; et al.
Summary: Multidrug resistance (MDR) proteins belong to the B subfamily of the ATP Binding Cassette (ABC) transporters, which export a wide range of compounds including pharmaceuticals. In this study, we used reverse genetics to study the role of all seven Plasmodium MDR proteins during the life cycle of malaria parasites. Four P. berghei genes (encoding MDR1, 4, 6 and 7) were refractory to deletion, indicating a vital role during blood stage multiplication and validating them as potential targets for antimalarial drugs. Mutants lacking expression of MDR2, MDR3 and MDR5 were generated in both P. berghei and P. falciparum, indicating a dispensable role for blood stage development. Whereas P. berghei mutants lacking MDR3 and MDR5 had a reduced blood stage multiplication in vivo, blood stage growth of P. falciparum mutants in vitro was not significantly different. Oocyst maturation and sporozoite formation in Plasmodium mutants lacking MDR2 or MDR5 was reduced. Sporozoites of these P. berghei mutants were capable of infecting mice and life cycle completion, indicating the absence of vital roles during liver stage development. Our results demonstrate vital and dispensable roles of MDR proteins during blood stages and an important function in sporogony for MDR2 and MDR5 in both Plasmodium species. Abstract : The role of MDR transporters of the ABC superfamily was evaluated in Plasmodium by targeting seven transporter genes, of which three could be successfully deleted. Loss of P. falciparum MDR2 results in reduced asexual growth, while in P. berghei this was the case for MDR3 and MDR5. Interestingly, deletion of MDR2 and MDR5 causes a reduction in oocyst and sporozoite production in both species, indicating a role for ABC transporters in transmission stages.